2018
DOI: 10.1080/09658211.2018.1474929
|View full text |Cite
|
Sign up to set email alerts
|

Investigating whether maternal memory specificity is indirectly associated with child memory specificity through maternal reminiscing

Abstract: Maternal reminiscing and remembering has a profound influence on the development of children's autobiographical remembering skills. The current study investigated the relationships between maternal memory specificity, maternal reminiscing and child memory specificity. Participants consisted of 40 mother-child dyads. Children's age ranged between 3.5 and 6 years. Mothers and children participated in individual assessments of autobiographical memory specificity. Dyads participated in a joint reminiscing task abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 43 publications
3
14
1
Order By: Relevance
“…As children learn from their mothers what, how, and why to remember (Ross & Wang, 2010) and maternal elaboration is strongly associated with child memory elaboration, it seems likely that maternal memory specificity is also significantly associated with child memory specificity. In support of this, Jobson et al (2018) recently provided initial support for a positive moderate relationship between mother and child memory specificity. However, further research in this area is still needed.…”
Section: The Present Studymentioning
confidence: 89%
See 1 more Smart Citation
“…As children learn from their mothers what, how, and why to remember (Ross & Wang, 2010) and maternal elaboration is strongly associated with child memory elaboration, it seems likely that maternal memory specificity is also significantly associated with child memory specificity. In support of this, Jobson et al (2018) recently provided initial support for a positive moderate relationship between mother and child memory specificity. However, further research in this area is still needed.…”
Section: The Present Studymentioning
confidence: 89%
“…The AEED is a series of Likert scales (ranging from 1 to 9, with high scales indicating higher levels of the behavior), which assess the overall affective quality of mother-child conversation. Following Valentino et al (2014) and Jobson et al (2018), mothers were rated on their (a) focus on discussion of child's emotional experiences; (b) acceptance and tolerance to child's thoughts and feelings; (c) involvement and reciprocity to keep child engaged in conversation; (d) resolution of negative feeling and emphasis on child's coping, strength and well-being; (e) structuring and elaboration to assist child's provision of narratives; (f) adequacy of the narrative topics; and (g) coherence of the stories coconstructed. Inter-rater agreement between the two coders was established based on the instruction provided in the AEED manual.…”
Section: Mother-child Reminiscingmentioning
confidence: 99%
“…Maltreating mothers may have experienced trauma during their own childhood that puts them at-risk for AMS, psychological, and socioemotional impairments . Indeed, one recent study has reported significant indirect effects of maternal AMS on child AMS through the affective quality of maternal reminiscing in a typically developing sample (Jobson et al, 2018). Investigations incorporating children's concurrent socioemotional (e.g., attachment security, emotional knowledge) and psychological functioning (e.g., depressive symptomology) would also be valuable in advancing theoretical accounts of AMS.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on the sociocultural theory of autobiographical memory development (Nelson & Fivush, 2004), which emphasizes the importance of early mother-child discussions about past experiences (i.e., reminiscing) in fostering children's autobiographical memory, the developmental psychopathology model of OGM posits that maternal reminiscing may facilitate children's AMS and that impoverished maternal reminiscing among at-risk families may be a critical mediator through which early traumatic experiences exert influence on reduced AMS (also see Salmon & Reese, 2015). Emerging empirical evidence demonstrating an association between maternal reminiscing and AMS among typically developing preschoolers provides initial support for the developmental psychopathology model (Jobson, Burford, Burns, Baldry, & Wu, 2018;McDonnell, Valentino, Comas, & Nuttall, 2016;Valentino, McDonnell, Comas, & Nuttall, 2018;Valentino et al, 2014). However, the association between maternal reminiscing and children's AMS has yet to be evaluated in atypical developmental contexts, including among maltreating families.…”
mentioning
confidence: 99%
See 1 more Smart Citation